Is not workplace gossip bad? The effect of positive workplace gossip on employee innovative behavior - Dai, Yuping; Zhuo, Xiangzhi; Hou, Jie; Lyu, Bei (Frontiers in Psychology, 2022)
Purpose The purpose of this study is to examine the role of positive workplace gossip (PWG) in employee innovative behavior, whereby a mediating effect of employee loyalty is proposed in this relationship. The moderating effect of organizational trust (OT) is also examined on the indirect of PWG on employee innovative behavior through employee loyalty. Design/methodology/approach This research used a survey data of 327 employees from the enterprises selected from the Pearl River and Yangtze River Delta region of China. Based on the literature review, five main hypotheses were formulated and explored. The SPSS-Process Macro Plugin was used to analyze the hypothesized model. Findings Results show there is a positive and significant relationship between PWG and employee innovative behavior. This study also confirm that employee loyalty is an intervening variable and OT as a moderator. Practical implications Organizations should pay more attention to workplace gossip phenomena, encourage employees to take appropriate part in positive workplace gossip and to communicate positive information about other colleagues, and build an inclusive, open, sincere, and interdependent platform in the organization. Originality/value Employee innovative behavior plays an essential role in organization’s survival and development. Few studies have investigated PWG may promote employee innovative behavior through employee loyalty. The data, model, and findings of this research address the gap and complement the current state of knowledge.